Odpowiedzi

2010-02-16T19:58:33+01:00
A) (2x-3)-(x+5)+(x+4)= 4x+6
b)(3a-2)-(a+4)+(a-3)=5a-1
c) 4(2y-7y do kw.)-3(y do kw. - 3y)=8y-28y²-3y²+9y= 17y-31y²
d)-5(2b+3z)+2(2b-4z)=- 10b-15z+4b-8z=14b-23z

a) -8x+6y-2= -2(4x-3y+1)
b) 6a-12b+18c=6(a-2b+3c)
e)4/5x+3/5x+1/5=5/(4x+3x+1)
2010-02-16T20:03:08+01:00
Wykonaj działania.
a) (2x-3)-(x+5)+(x+4)=
2x-3-x-5+x+4
2x-3-5+4
2x-4

b)(3a-2)-(a+4)+(a-3)=
3a-2-a-4+a-3=
3a-2-4-3
3x-9

c) 4(2y-7y do kw.)-3(y do kw. - 3y)
8y-28y do kwadratu-3y do kwadratu+9y
17y-31y do kwadratu

d)-5(2b+3z)+2(2b-4z)
-10b-15z+4b-8z
-6b-23z


wyłacz wspólny czynnik przed nawias.

a) -8x+6y-2=2(-4x+3y-1)
b) 6a-12b+18c=6(a-2b+3c)
e)4/5x+3/5x+1/5=1/5(4x+3x+1)